Spurious Volatility in Historical Unemployment Data - Romer, Christina (Journal of Political Economy, 1986)
This paper shows that the stabilization of the unemployment rate between the pre-1930 and post-1948 eras is an artifact of improvements in data collection procedures. Prewar methods are used to construct postwar unemployment data that are consistent with the historical data. The constructed postwar series is nearly as volatile as the pre-1930 unemployment data. The constructed postwar data are systematically more volatile than the actual postwar data because the cyclical behavior of the labor force and productivity are misspecified in the construction procedures. The relationship between the actual and constructed postwar unemployment series is used to construct new historical data.